HIKOYALARDA TARIXIY HAQIQATNING AKS ETISHI - Amirqulova, Z.M. (SCIENCE and SOCIETY, 2024)
This article artistically interprets the historical figures of Uzbek literature of the period of independence. Also in the article, the period of independence is expressed on the basis of historical figures and historical facts, expressed in historical plots created in Uzbek literature.